Famine in Ireland: 1300-1900 - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2015)
This paper describes the history of famine in Ireland between c. 1300 and c. 1900. Inevitably, most of its focus is on the two 'great' famines of the early 1740s and 1846-52.
Keywords: N; N5; O1; 330; famine; economic history; Ireland